2012
DOI: 10.1136/archdischild-2012-302724.0142
|View full text |Cite
|
Sign up to set email alerts
|

142 Community-Based Follow-Up with/without Food Supplementation and/or Psychosocial Stimulation in the Management of Children with Moderate Acute Malnutrition in Bangladesh

Abstract: Abstractssuffered from diarrhea and fever than others. Children who attended at least five of the total six scheduled follow-up visits gained more in weight, length than those who attended fewer. Conclusions Community-based service delivery, especially including supplementary food with or without psychosocial stimulation, permits better rehabilitation of greater numbers of children with MAM compared to current hospital outpatients-based care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nonadherence or defaulting in the counselling/education group was also a problem for the study by Hossain et al They found that children who attended at least five of the six follow‐up visits gained more in weight (median: 0.86 vs. 0.62 kg, p = .002) and length (median: 2.4 vs. 2.0 cm, p = .009) than those who attended fewer times (M. I. Hossain & Ahmed, ; M. I. Hossain & Yasmin, ).…”
Section: Resultsmentioning
confidence: 99%
“…Nonadherence or defaulting in the counselling/education group was also a problem for the study by Hossain et al They found that children who attended at least five of the six follow‐up visits gained more in weight (median: 0.86 vs. 0.62 kg, p = .002) and length (median: 2.4 vs. 2.0 cm, p = .009) than those who attended fewer times (M. I. Hossain & Ahmed, ; M. I. Hossain & Yasmin, ).…”
Section: Resultsmentioning
confidence: 99%